"Sinologism, " or Anxiety of the Thinking Subject. Issue 1 (2nd January 2018) - Zhou, Yunlong
Editors' Abstract: This article first examines how Said's theory of Orientalism and postcolonialism traveled to China and what problems the "traveling theory" aroused in the field of China studies. It then views the rise of Sinologism as a response to the anxieties of cultural consciousness experienced by many Chinese intellectuals both at home and abroad, caught in the confrontation between Chinese and Western academic discourses. It also examines what contributions the theory of Sinologism has made to the urgent need for an indigenous conceptual methodology for China studies free from constraints of ideology and political agendas. While affirming the insights of Sinologism, it regrets the heavy dose of Western theory in the construction of Sinologism, which unwittingly produces an ironic effect in critiquing Western misrepresentation of China.